Selective neurectomy of the facial nerve with cross face nerve graft for treating post-paralytic facial nerve syndrome - Ko Nakao; Takako Fujii; Hisashi Sakuma (Archives of Plastic Surgery)
Although post-paralytic facial nerve syndrome (PFS) is a frequent sequela of partial facial palsy, no effective treatment is currently available. Herein, we report a case of a cross-face nerve graft technique with selective neurectomy of the facial nerve in a 52-year-old female with moderate PFS (especially oral-ocular synkinesis and facial contracture) and a House–Brackmann score grade III. Selective neurectomy resulted in the release of the synkinesis and contractures. Furthermore, we reinnervated the levator muscles of the upper lip and oral commissure by connecting contralateral facial nerve to the thick zygomatic branch of the facial nerve via a cross-face nerve graft, which allowed neural augmentation of the “smile muscle.” No obvious PFS recurrence was observed one year postoperatively. This procedure is expected to provide a new treatment option for improving PFS because it is effective and less invasive.